2014
DOI: 10.1007/s12206-014-1012-7
|View full text |Cite
|
Sign up to set email alerts
|

Fault diagnosis of rotating machinery based on kernel density estimation and Kullback-Leibler divergence

Abstract: Based on kernel density estimation (KDE) and Kullback-Leibler divergence (KLID), a new data-driven fault diagnosis method is proposed from a statistical perspective. The ensemble empirical mode decomposition (EEMD) together with the Hilbert transform is employed to extract 95 time-and frequency-domain features from raw and processed signals. The distance-based evaluation approach is used to select a subset of fault-sensitive features by removing the irrelevant features. By utilizing the KDE, the statistical di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…For more details about HT, please refer to Ref. [20]. The corresponding results are shown in Figure 14.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For more details about HT, please refer to Ref. [20]. The corresponding results are shown in Figure 14.…”
Section: Results and Analysismentioning
confidence: 99%
“…The raw vibration data were collected by an accelerometer that was mounted on the top of the gearbox. The data sampling rate was 20 kHz, and the data length was 4096 points [20]. Case 2: The experimental data are from the Case Western Reserve University [21].…”
Section: Experimental Rigsmentioning
confidence: 99%
“…As dimensionless indices, skewness, kurtosis, peak indicators, waveform index, pulse index, and margin index can be used to represent rolling bearing fault features. These quantities are widely used in mechanical fault diagnosis [2]. Kullback-Leibler (K-L) divergence is called relative entropy.…”
Section: Feature Calculationmentioning
confidence: 99%
“…Due to its widespread industrial applications, roller bearing fault diagnosis is critical to prevent catastrophic failure of machines, thereby preventing economic losses [1,2]. Status of rolling element bearings is typically monitored by processing vibration signals [3].…”
Section: Introductionmentioning
confidence: 99%
“…According to Zhang et al [29], previous studies have indicated that kernel density function selection does not significantly affect the results; however, bandwidth (h) significantly affects the results, and no perfect measure exists for its determination [30].…”
Section: Estimation Of the Geostatistical Density Of The Geo-datamentioning
confidence: 99%